Jogging, nordic walking and going for a walk - inter-disciplinary recommendations to keep people physically active in times of the covid-19 lockdown in Tyrol, Austria - Frühauf, A.; Schnitzer, M.; Schobersberger, W.; Weiss, G.; Kopp, M. (Current Issues in Sport Science, 2020)
Physical activity has a strong impact on physical and mental health. It prevents diseases, strengthens the immune system, and helps to reduce stress. Moreover, physical activity increases the psychological well-being, with outdoor exercise showing even more positive effects. In times when national regulations also restrict the possibilities for exercise, the authors—referring to scientifically sound findings and adhering to the current social distancing rules—recommend allowing moderate outdoor sports activities (jogging, Nordic walking, going for a walk) and the use of park trails, hiking trails, and forest roads in easy terrains.